Gastric Stem Cell and Cellular Origin of Cancer - Hata, Masahiro (Biomedicines, 2018)
Several stem cell markers within the gastrointestinal epithelium have been identified in mice. One of the best characterized is Lgr5 (leucine-rich repeat-containing G-protein coupled receptor 5) and evidence suggests that Lgr5+ cells in the gut are the origin of gastrointestinal cancers. Reserve or facultative stem or progenitor cells with the ability to convert to Lgr5+ cells following injury have also been identified. Unlike the intestine, where Lgr5+ cells at the crypt base act as active stem cells, the stomach may contain unique stem cell populations, since gastric Lgr5+ cells seem to behave as a reserve rather than active stem cells, both in the corpus and in the antral glands. Gastrointestinal stem cells are supported by a specific microenvironment, the stem cell niche, which also promotes tumorigenesis. This review focuses on stem cell markers in the gut and their supporting niche factors. It also discusses the molecular mechanisms that regulate stem cell function and tumorigenesis.